Al-Ahkam: Kategori dan Implementasi - Fitriani, Dhaifina (TAWAZUN: Journal of Sharia Economic Law, 2021)
Shari'a law is an order from Allah Swt that is related to the actions of mukallaf, whether in the form of demands, choices, or making something as a cause, condition, barrier, valid, null, rukhsah, or 'azimah. The law revealed by Allah Swt to humans aims for the benefit and safety of humans both in this world and in the hereafter. We will get this salvation if we obey Allah's laws consistently. The laws of Allah Swt that must be obeyed are in the nature of definite and undefined orders, orders to leave work with certainty and orders to leave work uncertainly such as whether to leave or not, and sometimes Allah SWT's law is optional. Sharia law 'is divided into taklifi law and wadh'i law. Taklifi law is a law that contains orders to be done or to be abandoned by mukallaf or which contains a choice between being done and left. There are five taklifi laws, namely obligatory, sunnah, permissible, makruh, and haram. While wadh'i law is a law that makes something as a cause for another, or a condition for something else or as a barrier for something else. Which includes the wadh'i law there are seven, namely cause, condition, barrier (mani'), rukhsah, azimah, and valid (al-Shihhah) and null (al-Buthlan). The judge (shari') is Allah Swt. Therefore all Muslims agree that the judge (source of law) is Allah Swt, so the applicable law is the law of Allah Swt.